Coinfection of Leishmania (Viannia) braziliensis and Streptococcus pneumoniae in multiple cutaneous lesions - Cortes, Paulo R. (2016)
Key learning points Cutaneous leishmaniasis is the most common clinical disease caused by all the Leishmania species that are pathogenic to humans. Other bacterial coinfections of Leishmania lesions have been described, but this is the first report of coinfection with Leishmania and S. pneumoniae. S. pneumoniae is also able to cause skin infections, for that reason the pneumococcal diagnosis could be underestimated in Leishmania lesions coinfected with bacterial pathogens, particularly in endemic areas. An accurate microbiological diagnosis of Leishmania coinfections is essential for a correct antimicrobial treatment of skin infections.. Pentavalent antimonials, such as meglumine antimoniate, are considered the first-line antimicrobial therapy for the treatment of leishmaniasis.